2016
DOI: 10.1159/000452745
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Percutaneous Coronary Intervention Outcomes of Patients with Chronic Kidney Disease in the Era of Second-Generation Drug-Eluting Stents

Abstract: Background: The following registry (Katowice-Zabrze retrospective registry) aimed to assess the influence of a chronic kidney disease (CKD) on long-term clinical outcomes in patients undergoing percutaneous coronary intervention (PCI) using either first-generation (DES-I) or second-generation (DES-II) drug-eluting stents. Methods: The study group consisted of 1,908 consecutive patients, of whom 331 (17.3%) had CKD. CKD was defined as an estimated glomerular filtration rate of <60 mL/min/m2. We evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that renal impairment is a significant prognostic predictor of mortality in patients with coronary artery disease. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that renal impairment is a significant prognostic predictor of mortality in patients with coronary artery disease. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…The benefits of second-over first-generation DES in the CKD population are unclear, with a retrospective analysis failing to demonstrate mortality benefits with the use of second-generation DES 18 , probably due to systemic factors which are recognised to worsen oxidative stress and systemic inflammation independently 19 . Other contributing factors include left ventricular dysfunction (LVD) which is associated with adverse outcomes post PCI 20 .…”
Section: Mortalitymentioning
confidence: 99%
“…However, the prognosis of patients with CKD undergoing PCI is unsatisfactory. [9][10][11][12] Previous studies have shown that increased serum levels of phosphate were associated with poor revascularization outcomes. 13 However, they only investigated patients undergoing regular dialysis with a short follow-up period.…”
Section: Introductionmentioning
confidence: 99%